Practical guide to rotational moulding - Crawford, R. J. (Roy James), 1949-; Kearns, M. P. (Mark P.) (Elsevier, 2021)
Practical Guide to Rotational Moulding, Third Edition, takes a step-by-step approach to rotomoulding, covering applications, moulds, machinery, materials, and design. This third edition has been thoroughly revised to include the latest advances, including novel materials and moulds, new products, and automation. The book begins with a chapter that introduces the rotational moulding process, analyses advantages and disadvantages, and explores common applications for rotomoulded products. The subsequent chapters provide detailed, methodical coverage of moulds, machinery, materials, and design for functionality, supported by clear illustrations and diagrams. Finally, challenges and future developments are discussed. This hands-on technical guide helps engineers, designers and practitioners to understand all aspects of rotomoulding, with the aim of producing performant end products and parts, with uniform wall thickness and potentially in complex shapes. The book is also of great interest to professionals across the plastics industry, as well as researchers and advanced students in plastics engineering, industrial design, mechanical engineering, chemical engineering, and materials science and engineering.